The Approach to Learning Through Play Helps 4-Year-Old Children Master the Number Concept: Pendekatan belajar melalui bermain membantu Penguasaan Konsep Nombor Kanak-Kanak 4 tahun - Ureng, Grace Uyang; Mamat, Nordin bin; Daud, Fatimah binti (Jurnal Pendidikan Bitara UPSI, 2022)
This study aims to see the effectiveness of the learning approach through play on 4-year-old children. This study was conducted to improve children’s understanding of the concept of numbers by conducting Throw, Find and Match activities. The target group for the researcher’s action research this time is 2 4-year-old children from Tadika Pasti al-husna located in Hulu Bernam district. The problem in this class is that children cannot identify the numbers 1 to 5 well. The specific objective of this study was to find the best teaching to help four-year-olds in recognizing numbers 1 to 5 by using a learning-through-play approach (Throw, Find and Match). The study design was an Action Research using qualitative methods. work, observation checklists and photographs. The data analyzed using Microsoft Words Reflection of the study showed teaching using a learning approach by helping children identify the numbers 1 to 5 well.